Nilai Karakter dalam Karya Seni Batik Ngawi Sebagai Muatan Pendidikan Seni Rupa di Sekolah Dasar - Susilowati, Sri; Lilik, Lilik; Chumdari, Chumdari; Karsono, Karsono (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to describe the character values in the batik art work with Ngawi’s distinctive historical and natural motifs as a content of art education in elementary schools. This study uses a descriptive qualitative research method with a hermeneutic approach. The subjects in the study were Ngawi batik craftsmen. The data collection techniques used were interviews, observation, and documentation of the batik craftsmen and the resulting batik motifs. The data analysis technique used the interactive model analysis technique of Miles and Huberman. The results showed that the character values contained in the phytecanthropus erectus motif were religious, hard work, creative, love for the country, and communicative. The character values contained in the teak tree motif were religious, tolerance, discipline, hard work, creative, independent, communicative, peace-loving, and responsibility. The character values contained in the rice plant motif were religious, disciplined, hard work, national spirit, love for the country, respect for achievement, and communicative.